Severe gastrointestinal cytomegalovirus infection in a patient diagnosed with late onset combined immunodeficiency - Georgina Sauqué Pintos; Arnau Antolí Gil; Gemma Rocamora Blanch; Renzo Avila Espinoza; Rosario Taco Sánchez; Núria Sabé Fernández; Xavier Solanich Moreno (European Journal of Case Reports in Internal Medicine, 2024)
Late onset combined immunodeficiency (LOCID) is a rare variant of common variable immunodeficiency (CVID), typically affecting adult patients who present with opportunistic infections (OI) and/or low CD4+ T lymphocytes. Diagnostic delay is common due to the rareness of this entity, increasing morbidity and mortality. We report on a 66-year-old male who developed a severe gastrointestinal cytomegalovirus (CMV) infection, refractory to antiviral treatment and anti-cytomegalovirus specific human immunoglobulin administration, with a fatal outcome due to an undiagnosed LOCID.